Investigation Of Tree Stands Of Public Spaces In Szeged - Takács, Ágnes; Kiss, Márton; Tanács, Eszter; Varga, Levente; Gulyás, Ágnes (Journal of Environmental Geography, 2015)
In urban areas vegetation (especially woody vegetation) is of utmost importance, since it affects the ecological conditions of the city. Urban trees play an important role in improving urban climate both at the local (city, district) and the micro-level (e.g. in public squares). Establishing and maintaining advanced and detailed information systems necessary for the management of urban tree stands is an important task of environmental and climate-conscious city management. Despite that, few of the Hungarian municipalities have a regularly updated tree database. The city of Szeged started efficient green space management in autumn 2013, when we started the creation of a detailed and up-to-date tree register for the public areas, which has been continuously expanded ever since. The survey of the present study covers the period of the growing season, from late spring to early autumn of 2013. All the trees are included in the survey and quite a number of data are recorded for each individual (e.g. species, age, size parameters, exact location, health status, etc.). The recorded data are paper-based, however they are included in a GIS-based green space inventory software, Greenformatic, where coordinates are associated to each object, while information on the state of the tree, its location and handling can be found in the attribute table. The trees included are mostly concentrated in the inner city of Szeged, but the surveys will gradually cover ever larger areas of the city. The results highlight the fact that the structural attributes of the different species’ populations are formed by the integrated effect of the species’ urban tolerance and planting policies of the past decades. The current database already allows highly complex analysis, which contributes to the well-being of city residents.